Inflation targeting in practice: The UK experience - John Vickers (Goethe University Frankfurt, Center for Financial Studies (CFS), 1999)
In this speech (given at the CFSresearch conference on the Implementation of Price Stability held at the Bundesbank Frankfurt am Main, 10. - 12. Sept 1998), John Vickers discusses theoretical and practical issues relating to inflation targeting as used in the United Kingdom doing the past six years. After outlining the role of the Bank s Monetary Policy Committee, he considers the Committee s task from a theoretical perspective, beforediscussing the concept and measurement of domestically generated inflation.
urn:nbn:de:hebis:30-9230
Keywords: 330